(untitled) (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
Quarter-life crisis is a critical phase commonly experienced by individuals in early adulthood, marked by confusion about life direction, pressure of expectations, and anxiety about the future. In the digital era, social media exacerbates this crisis through mechanisms of unhealthy social comparison and unrealistic life expectations. Psychological symptoms such as anxiety, FOMO, and impostor syndrome have become increasingly prevalent. In such conditions, philosophical reflection becomes essential as a form of existential recovery. Stoic philosophy, particularly the thoughts of Seneca, offers a practical approach through principles such as the dichotomy of control, negative visualization, and journaling, which help individuals reorganize their values and sense of direction. This study employs a qualitative approach based on literature review to examine the interrelation between the quarter-life crisis, the influence of social media, and the relevance of Stoicism. The findings indicate that Stoicism is not merely an ancient philosophical heritage, but a contextual and applicable guide for the modern generation. Its philosophical values contribute to building mental resilience, inner tranquility, and wisdom in facing life’s pressures. Thus, this article asserts that philosophy can serve as a meaningful space of recovery for those seeking direction amidst the turbulence of contemporary life.